Cyclodextrin–silica hybrid materials: synthesis, characterization, and application in pesticide aqueous removal - Baigorria, Estefanía; Carvalho, Lucas Bragança; Alves Pinto, Luciana Matos; Fraceto, Leonardo Fernandes (Frontiers in Chemistry, 2024)
Introduction Overusing and misusing pesticides, including paraquat (PQ), have led to numerous environmental contamination complications. PQ is an emerging bio-accumulative contaminant that is present in environmental aqueous matrices. Adsorption techniques are part of a set of technologies applied in ecological remediation, known for their high effectiveness in removing aqueous PQ. A study of the PQ adsorption capacity of three cyclodextrin–silica nanocomposites (α-CDSi, β-CDSi, and γ-CDSi) from contaminated waters is presented in this paper. Methods The cyclodextrin–silica nanocomposites were synthesized via an esterification reaction between the inorganic matrix and cyclodextrins (CDs) (α, β, and γ) and were characterized physicochemically by spectroscopic, thermal, and surface methods. Their PQ removal performance from contaminated aqueous media was studied under different experimental conditions. Results and Discussion The results showed a fast adsorptive response in removal treatment studies over time. Adsorption capacities of 87.22, 57.17, and 77.27 mg.g−1 were found for α-CDSi, β-CDSi, and γ-CDSi, respectively, at only 30 min of treatment. Thermodynamic studies indicated spontaneous and exothermic adsorption processes. The removal assays responded mainly to physisorption mechanisms with contributions from chemisorption mechanisms. Spectroscopic assays showed a strong interaction of PQ with the adsorbents used. Innovative CDSi nanocomposites have proven to be highly efficient in applying aqueous PQ remediation, thus proving to be sustainable adsorbents of contaminants of emerging importance worldwide.